Simulating hydrates in shallow marine sediments - Hardwick, Jack (2018)
With global energy needs growing alongside a drive to reduce carbon emissions, there is a demand for cleaner, alternative energy. Methane hydrates are one such resource that is being investigated with the goal of future potential exploitation. 99 % of this resource is found within marine environments where, particularly in shallow marine sediments, there is a concern that rising ocean temperatures may lead to widespread methane release as hydrate dissociates. Multi-component, multi-phase (MCMP) modelling can be used to forecast the behaviour of methane hydrate dissociation in these contexts. However, there is a lack of agreement across literature on how best to numerically solve and mathematically describe the hydrate dissociation problem. The objective of this PhD is to develop new numerical models from first principles using the Method of Lines (MOL) approach. The MOL is attractive because it takes advantage of widely available high quality, ordinary differential equation solvers. However, a significant challenge is that the MOL requires formulating the problem in terms of persistent primary dependent variables. A kinetic model was developed and used to simulate experimental data from a well studied hydrate dissociation experiment. This study improved on previous work by reconciling more of the dataset. A three-phase permeability model was developed for this purpose, which invokes a critical threshold whereby permeability is dramatically reduced in the presence of very small hydrate saturations. Due to numerical instability associated with upscaling the hydrate kinetics, the MOL is challenging to solve for regional scale problems using the kinetic model. An alternative model which maintains phases in equilibrium by removing the hydrate kinetics was therefore developed. Preliminary work applied this equilibrium model to a regional scale ocean warming driven hydrate dissociation problem. Permeability in the presence of hydrate is a strong function of pore morphology as hydrate grows within porous media. ...